Novel tumour antigens and the development of optimal vaccine design. Issue 2 (April 2018) - Brentville, Victoria A; Atabani, Suha; Cook, Katherine; Durrant, Lindy G
The interplay between tumours and the immune system has long been known to involve complex interactions between tumour cells, immune cells and the tumour microenvironment. The progress of checkpoint inhibitors in the clinic in the last decade has highlighted again the role of the immune system in the fight against cancer. Numerous efforts have been undertaken to develop ways of stimulating the cellular immune response to eradicate tumours. These interventions include the identification of appropriate tumour antigens as targets for therapy. In this review, we summarize progress in selection of target tumour antigen. Targeting self antigens has the problem of thymic deletion of high-affinity T-cell responses leaving a diminished repertoire of low-affinity T cells that fail to kill tumour cells. Thymic regulation appears to be less stringent for differentiation of cancer–testis antigens, as many tumour rejection antigens fall into this category. More recently, targeting neo-epitopes or post-translational modifications such as a phosphorylation or stress-induced citrullination has shown great promise in preclinical studies. Of particular interest is that the responses can be mediated by both CD4 and CD8 T cells. Previous vaccines have targeted CD8 T-cell responses but more recently, the central role of CD4 T cells in orchestrating inflammation within tumours and also differentiating into potent killer cells has been recognized. The design of vaccines to induce such immune responses is discussed herein. Liposomally encoded ribonucleic acid (RNA), targeted deoxyribonucleic acid (DNA) or long peptides linked to toll-like receptor (TLR) adjuvants are the most promising new vaccine approaches. These exciting new approaches suggest that the 'Holy Grail' of a simple nontoxic cancer vaccine may be on the horizon. A major hurdle in tumour therapy is also to overcome the suppressive tumour environment. We address current progress in combination therapies and suggest that these are likely to show the most promise for the future.